2020
DOI: 10.3390/cells9102154
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-Terminal Kinase as a Therapeutic Target in Experimental Autoimmune Encephalomyelitis

Abstract: c-Jun N-terminal kinase (JNK) is upregulated during multiple sclerosis relapses and at the peak of experimental autoimmune encephalomyelitis (EAE). We aim to investigate the effects of pharmacological pan-JNK inhibition on the course of myelin oligodendrocyte glycoprotein (MOG35-55) EAE disease using in vivo and in vitro experimental models. EAE was induced in female C57BL/6JRj wild type mice using MOG35-55. SP600125 (SP), a reversible adenosine triphosphate competitive pan-JNK inhibitor, was then given orally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In addition, increased JNK phosphorylation, indicative of JNK signalling, was found in the acute disease phase of experimental autoimmune encephalomyelitis rats, an animal model mimicking neuroinflammation in MS [ 59 ]. Given the importance of the JNK pathway in pathological conditions, pan-JNK inhibition has been proposed as a novel treatment strategy for diseases associated with neurodegeneration and neuroinflammation [ 60 , 61 ] and, thus, might also be of advantage in the context of X-ALD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased JNK phosphorylation, indicative of JNK signalling, was found in the acute disease phase of experimental autoimmune encephalomyelitis rats, an animal model mimicking neuroinflammation in MS [ 59 ]. Given the importance of the JNK pathway in pathological conditions, pan-JNK inhibition has been proposed as a novel treatment strategy for diseases associated with neurodegeneration and neuroinflammation [ 60 , 61 ] and, thus, might also be of advantage in the context of X-ALD.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental autoimmune encephalomyelitis: Active MOG 35–55 EAE was induced in 8–12 weeks-old female GR wt and GR lck mice following our previously described protocol [ 23 , 26 ]. Briefly, animals were immunized by subcutaneous injection of 100 µg MOG 35–55 peptide (Institute of Medical Immunology, Charité, Berlin, Germany) in PBS (VWR, PA, USA) emulsified in complete Freund’s adjuvant containing 100 µg mycobacterium tuberculosis (Difco, MA, USA), followed by 200 ng pertussis toxin (Quadratech, Eastbourne, UK, intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al found that JNK was overactivated in chronic active MS plaques [134]. Bagnoud et al also found that the phosphorylated JNK is increased during demyelination-triggered MS [135]. During the progression of MS, the phosphorylation of JNK by ASK1 plays critical roles in multiple processes, such as oligodendrocyte destruction, demyelination, neuroinflammation, immune dysregulation through T cell activation (T cell apoptosis), and oxidative damage.…”
Section: Abnormal Activation Of the Jnk Pathway In Multiple Sclerosismentioning
confidence: 99%
“…In addition to the TLR (Toll-like receptor), other factors, including reactive oxygen species (ROS), oxidative stress, and inflammation, can activate ASK1 during MS progression [137]. These reports indicate that the over-activated ASK1-MKK4/7-JNK signaling axis plays a critical role in the pathogenesis of MS; that is, deregulated JNK signaling contributes to MS progression [134,135,137].…”
Section: Abnormal Activation Of the Jnk Pathway In Multiple Sclerosismentioning
confidence: 99%